2019
DOI: 10.1029/2018jc014843
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Statistical Features of Internal Solitary Waves on the Continental Slope in the Northern South China Sea Derived From Mooring Observations

Abstract: For investigation of internal solitary waves (ISWs) in the South China Sea (SCS), most cruise observations are concentrated from Luzon Strait to Dongsha Atoll in the northeastern SCS but few on the continental slope far away from the west of Dongsha Atoll. In this study, we use 1‐year long mooring data to determine dynamic and statistical features of the ISWs on the shelf slope of the northwestern SCS. The analysis results of the mooring data reveal that the ocean internal waves on the shelf slope of the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…According to the study of the vertical structure of the internal solitary wave (Geng et al, 2019), the maximum amplitude of the internal solitary wave is 70 m, which is located at a water depth of 100 m. As the water depth increases, the amplitude gradually decreases. According to Chen et al (2019), the maximum amplitude of the mode-one internal solitary wave found near the Dongsha Atoll is 87 m, which is similar to the amplitude of the internal solitary wave. In addition, Ramp et al (2004) observed many internal solitary waves in the east of Dongsha islands and they showed that the amplitude of the internal solitary waves ranged from 29 to 140 m. We conclude that seismic reflection data are a useful and accurate tool to observe the internal solitary wave amplitudes.…”
Section: Internal Solitary Wave In the Stacked Seismic Sectionmentioning
confidence: 65%
“…According to the study of the vertical structure of the internal solitary wave (Geng et al, 2019), the maximum amplitude of the internal solitary wave is 70 m, which is located at a water depth of 100 m. As the water depth increases, the amplitude gradually decreases. According to Chen et al (2019), the maximum amplitude of the mode-one internal solitary wave found near the Dongsha Atoll is 87 m, which is similar to the amplitude of the internal solitary wave. In addition, Ramp et al (2004) observed many internal solitary waves in the east of Dongsha islands and they showed that the amplitude of the internal solitary waves ranged from 29 to 140 m. We conclude that seismic reflection data are a useful and accurate tool to observe the internal solitary wave amplitudes.…”
Section: Internal Solitary Wave In the Stacked Seismic Sectionmentioning
confidence: 65%
“…In comparison with single soliton, NLIW packets are more common in field observations (e.g., Stanton & Ostrovsky, 1998) and/or satellite images (e.g., Brandt et al, 1996;Zheng et al, 2007). Apel (2003) and Chen et al (2019) suggested that a NLIW packet solution can be expressed by the dnoidal Jacobian elliptic functions. Therefore, the analytical solution of two NLIW packets, propagating in opposite directions (see Figure 1a), is written as…”
Section: Solution For Nliw Packetsmentioning
confidence: 99%
“…where 𝐴𝐴 𝐴𝐴𝑖𝑖 = 2 ∕𝐿𝐿 𝑖𝑖 is the wavenumber; 𝐴𝐴 𝐴𝐴𝑖𝑖 is the characteristic half-width of the leading wave in a NLIW packet; 𝐴𝐴 𝐴𝐴 2 is the nonlinear parameter, which is ranging from 0 to 1 (see Chen et al, 2019). 𝐴𝐴 𝐴𝐴𝑚𝑚 is a compensated quantity for amplitude.…”
Section: Solution For Nliw Packetsmentioning
confidence: 99%
“…The South China Sea (SCS), the largest semienclosed marginal sea in the western tropical Pacific Ocean, records the largest and fastest internal solitary waves (ISWs) in the global ocean (Huang et al., 2016; Klymak et al., 2006; Lien et al., 2014). A variety of in situ and satellite observations (Alford et al., 2010; Chen et al., 2018; 2019; Jackson, 2009; X. Li et al., 2013; Ramp et al., 2010; Wang et al., 2012) and theoretical and numerical models (Lai et al., 2019; Q. Li & Farmer, 2011; A. K. Liu et al., 2004; Xie et al., 2019; Zhao, 2014; 2020; Zhang et al., 2011; Zhao & Alford, 2006; Zheng et al., 2007) have been directed toward understanding and predicting the ISW's characteristics in the northern SCS over the last two decades (Alford et al., 2015; Guo & Chen, 2014). Although the background stratification and current have been found to play important roles in modulating these waves' characteristics and behavior (DeCarlo et al., 2015; Q. Li et al., 2016; Park & Farmer, 2013; Xie et al., 2015, 2016), how the background large‐scale mean motions, especially the typical wind‐driven oceanic circulations (Caruso et al., 2006; Su, 2004), affect them is still not well understood.…”
Section: Introductionmentioning
confidence: 99%